Diagnosing the rare: clinical experience in acardia twin recognition - a case report - Kamaruzaman, Nor Azam; Zulkifli, Siti Dzulaikha; Che Yusof, Mohd Daud (UniKL, 2024)
Twin Reversed Arterial Perfusion (TRAP) sequence or acardiac twin, is a rare condition in monochorionic twin pregnancies, presenting significant diagnostic and management challenges. Early detection of TRAP is crucial to improve foetal outcomes, particularly for the pump twin. We report the case of a 37-year-old gravida 5, para 3 + 1, who was initially misdiagnosed with a singleton pregnancy based on clinical and ultrasound examinations conducted at both primary and secondary health facilities. A marked discrepancy between the symphysiofundal height and ultrasound parameters later led to reassessment, revealing a twin pregnancy complicated by TRAP sequence. Radiofrequency ablation (RFA) was successfully performed on the acardiac twin at 28 weeks. The pregnancy ended at 30 weeks gestation with preterm birth, in which the pump twin was delivered alive while the acardiac twin was stillborn. This case highlights the importance of vigilant antenatal assessment, timely diagnosis, and intervention to optimise outcomes in TRAP sequence pregnancies.